(3YeOI GdWGdH hebfY GdQGZHs - (3Ydj Hf SdjeGf GdeQOGhjs
(3ChdgG (B:s
(3CeG HYO abO SfM HGdHGd ai GdebfY ef GdNdGa heGde jaUM s
(3BNQgG (B:s
(3hefgG ZGdH NUGFU GdfHi Udi Gddg Ydjg hSde GdeSJKfGg ef CMcGe GdCeI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdeJMa GdYQGb (B(35) s
Keywords: (3Gdabg GdMfHdjs